2015
DOI: 10.4028/www.scientific.net/msf.816.54
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tribological Properties of Ni-Base Coatings under Different Lubrication Conditions

Abstract: In order to improve the tribological properties of aluminum alloy cylinder wall, Ni-base coatings were fabricated by atmospheric plasma spraying on aluminum substrate. The composition, microstructure characterization and tribological properties of Ni-base coatings were investigated under different lubrication conditions. The results showed that as-sprayed Ni-based coatings were mainly consisted of γ-Ni solid solution, Ni3B, Cr7C3, Cr6C and Cr3B2 phase. The microstructure of coatings exhibited excellent deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Among those methods, thermal spraying is widely used in improving the strength, hardness and wear or corrosion resistance of metallic materials. In addition, our previous works prove that the thermal sprayed Ni-based coating possess better hardness, wear and corrosion resistance (Wang et al, 2015). Theoretically, the performance of 316 L in preventing tribocorrosion can also be improved by WC/Ni60 coating, which is mainly because that WC reinforcements perform well in hardness and Ni matrix possesses excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 88%
“…Among those methods, thermal spraying is widely used in improving the strength, hardness and wear or corrosion resistance of metallic materials. In addition, our previous works prove that the thermal sprayed Ni-based coating possess better hardness, wear and corrosion resistance (Wang et al, 2015). Theoretically, the performance of 316 L in preventing tribocorrosion can also be improved by WC/Ni60 coating, which is mainly because that WC reinforcements perform well in hardness and Ni matrix possesses excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 88%
“…In fact, different thermal spray processes such as wire arc spray, plasma transfer arc, atmospheric plasma spray, as well as HVOF were applied to the internal area of the cylinder liners [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Kincarid and Witherspoon [ 11 ] developed the pulse Arc-Spray for the production of Al and Fe-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…He proved that flow of primary plasma gas has a strong influence on wear resistance as well as on the friction coefficient. Wang et al [ 35 ] showed that the plasma spraying of nickel on aluminum cylinder liners decreased the friction coefficient without the necessity of a honing process. The surface finish by honing thermally sprayed coatings was investigated by Hoffmeister et al [ 36 ].…”
Section: Introductionmentioning
confidence: 99%